Factors Influencing Student-Athletes' Identity: A Multilevel Regression and Poststratification Approach. Issue 2 (April 2020) - Quinaud, Ricardo T.; Gonçalves, Carlos E.; Capranica, Laura; Carvalho, Humberto M.
We considered identity variation among Brazilian university student-athletes in relation to their gender, sport type, competition level, and university type. Participants were 506 student-athletes (219 males and 287 females) from public and private Brazilian universities, competing in team and individual sports, at local, state, and national levels. We used multilevel regression and poststratification to estimate each participant's identity from the aforementioned variables. Gender and sport type were not associated with any substantial identify variation, but there were higher values on Baller Identity Measurement Scale dimensions for student-athletes from public versus private universities, and student-athletes competing at the highest level had lower Baller Identity Measurement Scale values compared to peers competing at lower levels. Overall, university type and sport competitive level were the contextual factors that most influenced Brazilian student-athletes' identities.